Association Nutritional Status with Sarcopenia and Hypertension Among Adult in Semarang - syauqy, ahmad syauqy syauqy (Universitas Aisyah Pringsewu, 2024)
ABSTRACT Sarcopenia, characterised by a gradual decline in muscle mass and strength, and hypertension, which is a major risk factor for cardiovascular disease, pose complex challenges in health management. Both are influenced by various factors, including nutritional status. This study aimed to explore the relationship between nutritional status and the development of sarcopenia and hypertension in an elderly population. The research method was an analytical observational study with a cross-sectional approach conducted at Pegandan and Bululor health centres. Data were collected through anthropometric measurements, nutritional status, physical activity level, and blood pressure. Data were analysed using statistical software for descriptive and inferential statistics. The results showed a correlation between poor nutritional status and increased risk of sarcopenia and hypertension in the elderly population. The conclusion of this study emphasises the importance of early detection and appropriate intervention in addressing sarcopenia and hypertension to improve quality of life and overall health in the elderly population.